2009
DOI: 10.4314/tjs.v31i1.18405
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in water from TPC sugarcane plantations and environs, Kilimanjaro region, Tanzania

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Another study in Nicaragua showed high concentrations of DDT and its metabolites in the dry period (Hellar & Kishimba ). The highest concentrations in the dry period may relate to the physicochemical characteristics of water insolubility of OCPs (Hamilton & Crossley ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Nicaragua showed high concentrations of DDT and its metabolites in the dry period (Hellar & Kishimba ). The highest concentrations in the dry period may relate to the physicochemical characteristics of water insolubility of OCPs (Hamilton & Crossley ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the monitored compounds, seven of them were detected in water samples, while eight of them were detected in the sediment samples summarised in Table 6. (Hellar and Kishimba, 2005). Concentrations of the other detected OCP were very low in both water and sediment samples.…”
Section: Organochlorine Pesticide Residues (Ocp)mentioning
confidence: 88%
“…Analysis of surface waters collected close to the plantations in the past revealed contamination by different types of pesticide residues (Hellar-Kihampa, 2011;Hellar and Kishimba, 2005). The regions are also among the few areas that produce flowers for export in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of the environment with pesticide residues in environmental matrices could result in water pollution and thus endangering human health and non-target species. Cases of water pollution as well as soil and food contamination in Tanzania and elsewhere have been documented (Henry and Kishimba, (2002); Hellar et al, 2005;Mihale, 2004;Aktar et al, 2009;Kihampa et al, 2010aKihampa et al, , 2010bChowdhury et al, 2012) and some health effects have been correlated with pesticide pollution (Ngowi, 2002;Agenda, 2006). As part of this review, surface water and ground water is the compartment of concern.…”
Section: Pesticide Pollutionmentioning
confidence: 99%